Extracellular matrix-based sticky sealants for scar-free corneal tissue reconstruction. (January 2023) - Kim, Hyeonji; Jang, Je-Hwan; Han, Wonil; Hwang, Hyun-Jeong; Jang, Jinah; Kim, Joon Young; Cho, Dong-Woo
Abstract: Regenerative medicine requires both tissue restoration and ease of compliance for clinical application. Considering this, sticky tissue sealants have been shown to have great potentials over surgical suturing and wound treatment. However, tissue sealants currently used pose challenges such as uncontrollable adhesion formation, mechanical mismatch, and lack of tissue restoration. A new sticky sealant based on gelatinized cornea-derived extracellular matrix (GelCodE) with a visible light-activating system is firstly being introduced in this study. De novo tissue regeneration relies on the matrisome in charge of tissue-organization and development within GelCodE while visible light-based photopolymerization with ruthenium/sodium persulfate rapidly induces covalent bonds with the adjacent tissues. The ease of not only in vivo application, biocompatibility, and biointegration, but also exceptional de novo tissue formation is demonstrated in this study. Interestingly, newly regenerated tissues were shown to have normal tissue-like matrices with little scar formation. Hence, this work presents a promising strategy to meet clinical demands for scar-free tissue recovery with superior ease of clinical application. Highlights: dECM-based sticky sealants were firstly developed. Liquid-typed GelCodE sealant compactly fits into the corneal wound site. The photopolymerization of GelCodE sealant utilizes non-toxic visible light. GelCodE sealant promotes scar-free corneal reconstruction leading to be transparent.